Tax Revenue in Sub-Saharan Africa : Effects of Economic Policies and Corruption - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 1998)
An analysis of data for 39 sub-Saharan African countries during 1985-96 indicates that the variations in tax revenue-GDP ratios within this group are influenced by economic policies and the level of corruption. Namely, these ratios rise with declining inflation, implementation of structural reforms, rising human capital (a proxy for the provision of public services by the government), and declining corruption. The paper confirms that the tax revenue ratio rises with income, and that elements of a country's tax base (such as the share of agriculture in GDP and the degree of openness) influence tax revenue.